z=e^((-x)*y)*y la ecuación
El profesor se sorprenderá mucho al ver tu solución correcta😉
Solución
/ -x*y\ / -x*y\
z1 = I*im\y*e / + re\y*e /
z1=re(ye−xy)+iim(ye−xy)
z1 = re(y*exp(-x*y)) + i*im(y*exp(-x*y))
Suma y producto de raíces
[src]
/ -x*y\ / -x*y\
I*im\y*e / + re\y*e /
re(ye−xy)+iim(ye−xy)
/ -x*y\ / -x*y\
I*im\y*e / + re\y*e /
re(ye−xy)+iim(ye−xy)
/ -x*y\ / -x*y\
I*im\y*e / + re\y*e /
re(ye−xy)+iim(ye−xy)
/ -x*y\ / -x*y\
I*im\y*e / + re\y*e /
re(ye−xy)+iim(ye−xy)
i*im(y*exp(-x*y)) + re(y*exp(-x*y))